Hard judicial choice - Cooper, Philip J. (New York, 1988)
This book, the first to attempt to view these cases from the perspective of district-court judges, examines some of these questions through five comparative case studies involving housing discrimination, school desegregation, mental health facilities, and the right to treatment, prison conditions, and policy/community relations. An introductory chapter presents a clear overview of the remedial decree process. Each of the following case studies is preceded by a chapter that sets the case in its legal, administrative, and political context..
Keywords: Judicial review of administrative acts-United States